A Pharmacotherapeutic Study of Yashtimadhu on Kasa Roga (AYUSHDHARA, 2022)
Now a day, many persons of all age groups are suffering from Kasa roga. In modern science, it is called as cough, which is a voluntary and involuntary act that clears the throat and breathing passage. In Charak Samhita, Kasa roga is described as disease and symptoms of many diseases. Kasa roga are of 5 types. These are Vataj, Pittaj, Kaphaj, Kshataj and Kshyaj. Yashtimadhu is the plants which have property to cure the Kasa roga. I had done clinical trial on 20 patients for 90 days. Results are as follows: This 20 patients was treated with Yashtimadhu churna with honey B.D., 1 patient did not completed the trial. Out of 19 patients, 12 patients i.e., 63.16% were cured, 5 patients i.e., 26.32% were moderately improved and 2 patients i.e., 10.53% showed mild improvement